2007
DOI: 10.1152/ajpgi.00348.2006
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin regulates the TFF2 promoter through gastrin-responsivecis-acting elements and multiple signaling pathways

Abstract: Trefoil family factor 2 (TFF2) is expressed in gastrointestinal epithelial cells where it serves to maintain mucosal integrity and promote epithelial repair. The peptide hormone, gastrin, stimulates acid secretion but also induces proliferation of the acid-secreting mucosa. Because the relationship between these peptides of overlapping function is not understood, we chose to investigate the regulatory effect of gastrin on TFF2 expression. The expression of mRNA and protein of TFF2 was determined by RT-PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…In contrast, TFF2 expression was up-regulated by EGF in IEC-6 cells only; whereas TFF1 expression was not altered following EGF treatment. The up-regulation of TFF2 by EGF is in agreement with a previous report using AGS-E cells [47]. The corresponding TFF proteins are well known for their key roles during regeneration and repair of mucous epithelia, particularly by enhancing restitution [4].…”
Section: Egf Induces Expression Of Genes Involved In Emt and Metastasissupporting
confidence: 90%
“…In contrast, TFF2 expression was up-regulated by EGF in IEC-6 cells only; whereas TFF1 expression was not altered following EGF treatment. The up-regulation of TFF2 by EGF is in agreement with a previous report using AGS-E cells [47]. The corresponding TFF proteins are well known for their key roles during regeneration and repair of mucous epithelia, particularly by enhancing restitution [4].…”
Section: Egf Induces Expression Of Genes Involved In Emt and Metastasissupporting
confidence: 90%
“…Antibodies to ␣-tubulin were purchased from Oncogene Science, Inc. (Cambridge, MA). Rabbit anti-TFF2 antibodies to a carboxyl-terminal peptide (16 amino acids) of hTFF2 (which also recognize mTFF2) were developed previously and characterized in our laboratory (31).…”
Section: Methodsmentioning
confidence: 99%
“…It was recently shown that expression of TFF2 is enhanced by gastrin, which induces secretion of HCl in the stomach, suggesting a self-protective loop to ensure mucosal protection from the secreted HCl [153].…”
Section: Regulation Of Expressionmentioning
confidence: 99%